Associations between a laboratory frailty index and adverse health outcomes across age and sex - Blodgett, Joanna M. (Aging Med (Milton), 2019)
OBJECTIVE: Early frailty may be captured by a frailty index (FI) based entirely on vital signs and laboratory tests. Our aim was to examine associations between a laboratory‐based FI (FI‐Lab) and adverse health outcomes, and investigate how this changed with age. METHODS: Up to 8988 individuals aged 20+ years from the 2003‐2004 and 2005‐2006 National Health and Nutrition Examination Survey cohorts were included. Characteristics of the FI‐Lab were compared to those of a self‐reported clinical FI. Associations between each FI and health care use, self‐reported health, and disability were examined in the full sample and across age groups. RESULTS: Laboratory‐based FI scores increased with age but did not demonstrate expected sex differences. Women aged 20‐39 years had higher FI scores than men; this pattern reversed after age 60 years. FI‐Lab scores were associated with poor self‐reported health (odds ratio[95% confidence interval]: 1.46[1.39‐1.54]), high health care use (1.35[1.29‐1.42]), and high disability (1.41[1.32‐1.50]), even among those aged 20‐39 years. CONCLUSION: Higher FI‐Lab scores were associated with poor health outcomes at all ages. Associations in the youngest group support the notion that deficit accumulation occurs across the lifespan. FI‐Lab scores could be utilized as an early screening tool to identify deficit accumulation at the cellular and molecular level before they become clinically visible.